A Model for Inclusive Education in Indonesia: The Lazuardi Global Islamic School - Madanih, Rahmawati (Jurnal Ilmu Sosial Indonesia (JISI), 2023)
Abstract. Inclusive education has gained momentum in the last few years as it becomes the buzzword in the vernacular of the Indonesia’s education sector, especially among the educators and education providers in Indonesia. Inclusive education requires education providers to provide quality and accessible education for students with disabilities. This article examines the practice of inclusive education at the Lazuardi Global Islamic School. It is located at the border of West Java and the capital city of Jakarta and is considered as one of the first educational institutions to offer inclusive education within an Islamic educational setting. The article begins with an overview of the inclusive education program offered since 1994 and the progressive orientation of the school’s organization, management, teachers’ educational development and training, in addition to an inclusive curriculum development, that has enabled implementation of an inclusive education. Based on qualitative research and extensive interviews with the school’s leaders, teachers, health professional staffs, parents, and students, this article discusses and analyses the experience of Lazuardi School in implementing inclusive education. The story of Lazuardi can be used as a reference for other Islamic education providers to offer inclusive Islamic education system. Keywords: Inclusive Education, Students with Disabilities, Special Education Needs, Islamic Schools, Indonesia. Abstrak. Pendidikan inklusif mendapat momentum dalam beberapa tahun terakhir sebagai istilah yang dipakai dalam bahasa sehari-hari di bidang pendidikan, terutama di kalangan pendidik dan penyelenggara pendidikan di Indonesia. Pendidikan inklusif mensyaratkan penyelenggara pendidikan untuk menyediakan pendidikan yang berkualitas dan dapat diakses oleh siswa penyandang disabilitas. Artikel ini mengkaji praktik pendidikan inklusif di Lazuardi Global Islamic School. Lembaga pendidikan ini terletak di perbatasan Jawa Barat dan ibukota Jakarta dan dianggap sebagai salah satu lembaga pendidikan pertama yang menawarkan pendidikan inklusif dalam lingkungan pendidikan bernuansa Islam. Paper ini diawali dengan penjelasan mengenai ikhtisar program pendidikan inklusif yang dimulai sejak 1994 dan orientasi progresif organisasi sekolah, manajemen, pengembangan dan pelatihan pendidikan guru, di samping pengembangan kurikulum inklusif, yang memungkinkan pelaksanaan pendidikan inklusif. Berdasarkan penelitian kualitatif dan wawancara ekstensif dengan pimpinan sekolah, guru, staf profesional kesehatan, orang tua, dan siswa, penulis membahas dan menganalisis pengalaman Sekolah Lazuardi dalam mengimplementasikan pendidikan inklusif. Kisah Lazuardi dapat dijadikan referensi bagi penyelenggara pendidikan Islam lainnya untuk menawarkan sistem pendidikan Islam inklusif. Kata Kunci: Pendidikan Inklusif, Siswa Penyandang Cacat, Kebutuhan Pendidikan Khusus, Sekolah Islam, Indonesia.